2019
DOI: 10.25176/rfmh.v19.n2.2070
|View full text |Cite
|
Sign up to set email alerts
|

Factores De Riesgo Asociados a Pie Diabético en El Hospital PNP Luis N. Saenz, Año 2017

Abstract: Introducción: El pie diabético es una de las complicaciones más graves y frecuentes de la diabetes mellitus, por tal motivo es importante conocer los factores de riesgo que lo desencadenan. Objetivo: Determinar los factores de riesgo asociados a pie diabético en el hospital PNP Luis N. Sáenz, año 2017. Métodos: Estudio observacional, cuantitativo, retrospectivo, analítico, de casos y controles. La muestra la conformó 165 pacientes (55 casos y 110 controles) atendidos en el servicio de endocrinología en el año … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…Obesity and arterial hypertension were significant in univariate analysis but not in multivariate analysis. On the other hand, dyslipidemia behaved as a protective factor (OR: 0.24; CI 95% 0.11 -0.48) (26). The apparent contradiction of these outcomes with the international literature (35,36,39) may probably be explained by the size of the samples.…”
Section: Comorbiditiesmentioning
confidence: 85%
See 4 more Smart Citations
“…Obesity and arterial hypertension were significant in univariate analysis but not in multivariate analysis. On the other hand, dyslipidemia behaved as a protective factor (OR: 0.24; CI 95% 0.11 -0.48) (26). The apparent contradiction of these outcomes with the international literature (35,36,39) may probably be explained by the size of the samples.…”
Section: Comorbiditiesmentioning
confidence: 85%
“…A case-control study carried out by Arribasplata and Lena-Muñoz (26) showed a significant association between DF with PN (OR: 2.88, 95% CI: 1,45 -5,72) in univariate analysis. However, this association was not observed in multivariate analysis (p>0.05).…”
Section: Peripheral Neuropathymentioning
confidence: 96%
See 3 more Smart Citations